Order Independence for Iterated Weak Dominance - Leslie McFarland-Marx; Jeroen M. Swinkels (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
In general, the result of the elimination of weakly dominated strategies depends on order. We find a condition, satisfied by the normal form of any generic extensive form, and by some important games which do not admit generic extensive forms, under which any two games resulting from the elimination of weakly dominated strategies (subject to no more eliminations being possible) are equivalent. We also extend our condition and result to the case of elimination by mixed strategies. The result strengthens the intuitive connection between backward induction and weak dominance. And, under our condition, some computational problems relating to weak dominance, which are gnerally complex, become simple.
Keywords: 330